Design and evaluation of a methodology to characterize the biopesticide activity of Bacillus thuringiensis native strains against Spodoptera frugiperda (Lepidoptera: Noctuidae) - RODRÍGUEZ, MARÍA; TORRES, LUIS E.; URIBE, DANIEL; CERÓN, JAIRO; ACOSTA, ALFREDO (Revista Colombiana de Entomología, 2001)
Bacillus thuringiensis (Bt), like a biological control agent, has some advantages, which make it attractive for an Integrated Pest Management program. The research about Bt is increasing each day; for instance new strains and commercial products with high biopesticide activity against local agricultural pest insects of different countries are rising. Spodoptera frugiperda (J.E Smith) is a very aggressive pest insect, which affects important agricultural crops in our country like com, cotton, sorghum, and rice. That insect is good to target to be controlled by native strains of Bt as long as it developed resistance to the conventional chemical insecticides. In this study, it was presented a methodology to evaluate the biopesticide activity of Colombian native strains of Bt against S frugiperda. lt was worked in lab conditions with first instar larvae on an artificial diet. The Bt aizawai HD137, which has the cry genes cry1Aa, cry1Ab, cry1B, cry1C y cry1D was used as biopesticide activity reference strain. twenty native strains from Colombian soils were evaluated by the designed methodology. lt was concluded that the bioassay methodology is sensitive, repetitive, efficient, and fast methodology, which can be used in similar tests. In addition, an important biopesticide activity, in four out of 20 strains evaluated, was found, which suggests a great diversity of strains and genes for d-endotoxin and the huge potential of these strains to be used in our country.